Caregiver burden and psychiatric morbidity among caregivers of children with thalassemia major: A cross-sectional study - Nisha Kanaiyalal Prajapati; Mukesh Jyantilal Samani; Arpit Madhusudanbhai Jani (Annals of Indian Psychiatry, 2021)
Background: Caregivers of children with thalassemia major experience higher caregiver burden and psychiatric morbidity. Aims: The aims of this study were as follows: (1) to assess the caregiver burden and psychiatric morbidity among caregivers of children with thalassemia major and (2) correlation between caregiver burden and psychiatric morbidity. Settings and Design: This was an observational, cross-sectional study carried out at the tertiary care hospital setup among 245 caregivers of children with thalassemia major. Subjects and Methods: Sociodemographic details of children and their caregivers and clinical variables of children were obtained. The Caregiver Burden Scale and General Health Questionnaire (GHQ)-12 were applied. Psychiatric diagnosis was made after clinical interview as per the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition. Statistical Analysis Used: Chi-square test, t-test, analysis of variance, and Pearson coefficient correlation were used for statistical analysis. Results: 33.06% were having severe burden, 30.61% moderate-to-severe burden, 27.34% mild-to-moderate burden, and 8.97% were having little or no burden. 13.46% of caregivers had psychiatric illness, out of which 8.57% had major depressive disorder, 4.08% generalized anxiety disorder, and 0.8% alcohol use disorder. “Weakly positive correlation” (P = 0.0284) was found between GHQ score and burden score. Conclusions: Higher caregiver burden and presence of psychiatric morbidity among caregivers of thalassemia children suggest that caregivers should be screened at regular intervals for early detection and management of psychiatric morbidity. Social and professional networks for psychosocial support and self-help groups should be planned for caregiver burden.